OPTIMIZATION OF CHLORELLA SP. CELL GROWTH IN OUTDOOR OF PHOTOBIOREACTOR AND STUDY OF ETHYL TERTIARY BUTYL ETHER SYNTHESIS - Harnaldo Putra, Billy
Previous studies have reported that tropical marine microalgae of Chlorella sp. produce carbohydrates that can be converted into ethanol. Furthermore, ethanol and isobutylene can be converted into ethyl tertiary butyl ether (ETBE) with help of an acid catalyst. As it has been known, ETBE is useful to increase octane number of gasoline due to the oxygen content of ETBE is capable of improving the fuel-burning efficiency. The purpose of the present study was to improve the biomass productivity of Chlorella sp. as a source of carbohydrate, and to study ETBE synthesis of ethanol and isobutylene. The research steps included production of biomass Chlorella sp. by using indoor and outdoor photobioreactors with varying different types of nutrients of medium (such as Walne medium and fertilizer medium including NPK, PSCa, and NPK with additional Na2SiO3.5H2O), cultivation techniques (such as Batch and fed-Batch techniques), and seawater sources (such as original and artificial seawaters). Parameters for Chlorella sp. cell-growth conditions in indoor and outdoor photobioreactors were salinity, pH, aeration, temperature, and light intensity. Biomass of Chlorella sp. was harvested by the techniques either autoflocculattion using NaOH or filtration using commercial PVA membrane. Total carbohydrate content of dry biomass was determined by the DNS method. To synthesis ETBE, isobutylene obtained from isobutyl alcohol in concentrated sulphuric acid or from crude-C4 was reacted with ethanol gas with help of Amberlyst-15 at 74 °C, followed by condensation of the ETBE product. The results showed that the growth of Chlorella sp. cells in Walne medium indoor was optimum at the 12th day with cell density of 25.48 × 106 cells/mL or wet cell of 23.18 g/L culture, and total carbohydrate content of 38.3% (w/w). Moreover, the optimum cell densities obtained from culture in fertilizer media of 5% Rosasol-Even NPK 18-18-18 and 5% Grow More NPK 20-20-20 combined by Grow More Nutra+Zorb Calcium 5% (1:1) were 25.37 and 24.3×106 cells/mL, respectively, or biomass density of 29.86 and 18.62 g wet cells/L, respectively, with total carbohydrate content of 76.25 and 61.25 % (w/w) respectively. The cell densities of Chlorella sp. obtained from in both Batch and fed-Batch cultures were 29.7 and 36.85×106 cells/mL, respectively, or biomass density of 20.82 and 54.1 g/L, respectively, with total carbohydrate content of 40.41 and 52.5% (w/w), respectively. The total carbohydrate content obtained from cell cultures in original and artificial seawater medium was 48.75 and 45.00% (w/w), respectively. The density of Chlorella sp. cells in medium Walne and 5% Grow More NPK 20-20-20 combined by 5% Nutra Grow More+Zorb Calcium in outdoor photobioreactors for 12 d was 19.12 and 17.65×106 cells/mL, respectively, with total carbohydrate content of 50.83 and 56.67% (w/w), respectively. With respect to synthesis ETBE, 11 mL ethanol was successfully converted into 6.2 mL products. GCMS analysis of the product at retention time of 1.887 min showed the fragment peaks of ETBE for ions (m/z) of 57 (C4H9), 59 (C4H11), and 87 (C5H11O). Overall results of the present study can be concluded that the biomass productivity using outdoor photobioreactors was lower than that using indoor photobioreactors, but the total carbohydrate content obtained from outdoor photobioreactors was higher than that from indoor photobioreactors. Meanwhile, the optimized ETBE synthesis further was necessarily to be carried out.